2022
DOI: 10.1177/03000605221125050
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and molecular analyses of the HbS allele among the Sudanese population

Abstract: Objective The purpose of this study was to perform hematological and molecular analyses of the HbS allele of the hemoglobin subunit beta gene in the Sudanese population. Methods This was a descriptive cross-sectional study. Hematological parameters and fetal hemoglobin (HbF) levels were assessed in all participants. Data were gathered through the use of questionnaires and laboratory investigations. The βS-globin haplotypes, S allele distributions, and hematological parameters with HbF levels were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The study also revealed that, the Sudanese group from Northern Kordofan lacked the Arab-Indian haplotype and two heterozygous versions of undisputed haplotypes were found in 17.3% of participants: SU/BA in 10.8% and CA/BE in 6.5%. 8 In this study and upon beta gene (HBB) entire sequencing, five patients (5%) showed a presence of Hb O-Arab mutation ((HBB):c.364G>A (p.Glu122Lys)).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The study also revealed that, the Sudanese group from Northern Kordofan lacked the Arab-Indian haplotype and two heterozygous versions of undisputed haplotypes were found in 17.3% of participants: SU/BA in 10.8% and CA/BE in 6.5%. 8 In this study and upon beta gene (HBB) entire sequencing, five patients (5%) showed a presence of Hb O-Arab mutation ((HBB):c.364G>A (p.Glu122Lys)).…”
Section: Discussionmentioning
confidence: 65%
“…The study also revealed that, the Sudanese group from Northern Kordofan lacked the Arab-Indian haplotype and two heterozygous versions of undisputed haplotypes were found in 17.3% of participants: SU/BA in 10.8% and CA/BE in 6.5%. 8 …”
Section: Discussionmentioning
confidence: 99%